Helmolds von Bosaupons longissimus. Archaologische Unterwasserausgrabungen bei den Briickenanlagen neben der slawischen und frühdeutschen Burg Olsborg im Grossen Ploner See (Norddeutschland) - Wilke, Gerard (Folia Praehistorica Posnaniensia, 2018)
The article is aimed at presentation of results of archaeological underwater excavations of remains of the early Medieval bridge on the stronghold island Oslborg. There are vestiges of the Slavic and early German stronghold on the Grosser Plòner Lake island near Plon in north Germany. This stronghold has been repeatedly mentioned by Adam of Bremen and Helmold of Bosau - the 11th and 12th century annalists. Underwater excavations, undertaken in two study zones of 75 square meters in total, resulted in discovery of the bridge remains which revealed themselves in the form of 228 posts being elements of its bearing construction placed on the lake bottom. Dendrochronological analysis of 79 posts indicates that the bridge was constructed in 975 AD and it was rebuilt many times afterwards. Trees for subsequent reconstructions were cut down in the years 994, 995, 1005, 1008, 1011, 1012, 1013, 1025 and for the last time in 1096 AD. The excavations revealed also an assemblage of Slavic and early German pottery as well as 56 artefacts including 14 spearheads and 6 axes. These military accessories can possibly be linked with the 1075, 1128 or 1139 war, mentioned by Helmold of Bosau. Bleile R. 1999 Vorbericht zu unterwasserarchàologischen Untersuchungen an einer Slawischen Briickenanlage im PlauerSee bei Quetzin, Landkreis Parchim (Mecklenburg-Vorpommern), „Nachrichtenblatt Arbeitskreis Unterwasserarchaologie” Bd. 5, S. 32-35. Bleile R. 2003 Briicken unter Wasser. Neue Ergebnisse zu slawischen Briicken und Bohlenwegen in Mecklenburg-Vorpommern, „Mitteilungen der Deutschen Gesellschaft fur Archàologie des Mittelalters und der Neuzeit” 14, S. 80-84. Freytag H.J. 1985 Die Lage der slawischen und friihen deutschen Burg Plon, „Zeitschrift der Gesellschaft für Schleswig-holsteinische Geschichte” Bd. 10, S. 27-52. Hucke K. 1952 Wo lag die wendische Burg Plune?, „Die Heimat” Bd. 59, S. 136—139. Kempke T. 1992 Slawen in Ostholstein. Ausgrabungen in Bosau am Ploner See, (in:) Der Vergangenheit auf der Spur. Archàologische Siedlungsforschung in Schleswig-Holstein, Hrsg. M. Miiller-Wille und D. Hoffmann, S. 141-162. Kempke T. 1998 Archàologische Beitràge zur Grenze zwischen Sachsen und Slawen im 8.-9. Jahrhundert, (in:) Studien zur Archàologie des Ostsseeraumes. Von der Eisenzeit zum Mittelalter (Festschrift Michael Miiller-Wille), Hrsg. A. Wesse, Neumiinster, S. 373-382. Mittelstàdt U. 1976 Die Entwicklung der Stadi Plon bis zum Ausgang des Mittelalters, „Jahrbuch tur Heimatkunde im Kreis Plòn-Holstein” Jg. 7, S. 5-34. Kiefmann H.M. 1978 Historisch-geographische Untersuchungen zur alteren Kulturlandschafts-entwicklung, (in:) Bosau. Untersuchung einer Siedlungskammer in Ostholstein unter Leitung von Hermann Hinz, „Offa-Biicher” Bd. 38. Kola A., Wilke G. 2000 Briicken vor 1000 Jahren. Unterwasserarchaologie bei der polnischen Herrscherpfalz Ostrów Lednicki, Toruń. Krambeck H.J. 1979 A numercial-topographical model of Lake Grofier Plòner See and its application to the calculation of Seiches, „Archiv Hydrobiological” Bd. 87-3, S. 262-273. Wilke G. 1985 Most wczesnośredniowieczny z Bobęcina kolo Miastka. Wstępne wyniki archeologicznych badań podwodnych i analiz dendrochronologicznych jego reliktów [Sum.: The early mediewal ages bridge of Bobącin near Miastko. Preliminary results of archaeological underwater investigations and dendrochronological analyses of its remains], „Acta Universitatis Nicolai Copernici”, Archeologia 11, Archeologia Podwodna 2, S. 3-26. Wilke G. 1995 Lokalizacja stanowisk archeologicznych pod lustrem wody na przykładzie Jeziora Płońskiego Wielkiego (Grosser Ploner See) w północno-zachodnich Niemczech [Sum.: Location of archaeological sites under water - level on the example of Płońskie Wielkie Lake (Grosser Ploner See) in North Germany], (in:) Archeologia podwodna jezior Niżu Polskiego, Hrsg. A. Kola, Toruń, S. 71-90. Wilke G. 1998 Archàologie unter Wasser. Untersuchungen der slawischen Briicken in Lednica-See bei der Insel Ostrów Lednicki (Polen), (in:) Studien zur Archàologie des Ostseeraumes. Von der Eisenzeit zum Mittelalter (Festschrift Michael Müller-Wille), Hrsg. A. Wesse, Neumünster, S. 195-203. Wilke G. 2000a Analiza chronologiczno-przestrzenna struktur palowych i próba rekonstrukcji mostu [Sum.: Chronological - spatial analysis of pile structures and an attempt of bridge reconstruction], (in:) Wczesnośredniowieczne mosty przy Ostrowie Lednickim, t. 1 : Mosty traktu gnieźnieńskiego, Hrsg. Z. Kurnatowska, Lednica-Toruń, S. 57-71. Wilke G. 2000b Briicken und Brückenbau im óstlichen Mitteleuropa um 1000, (in:) Europas Mitte um 1000. Beitrage zur Geschichte, Kunst und Archàologie, Hrsg. A. Wieczorek, H.M. Hinz, Handbuch zur Ausstellung, Stuttgart, S. 142-145.